A Radionuclide Generator of High-Purity Bi-213 for Instant Labeling - Stanislav Ermolaev; Aino Skasyrskaya; Aleksandr Vasiliev (MDPI AG, 2021)
A new two-column 225Ac/213Bi generator was developed specifically for using 225Ac containing an impurity of long lived 227Ac. The parent 225Ac was retained on the first Actinide Resin column, while 213Bi was accumulated on the second column filled with AG MP-50 resin via continuous elution and decay of intermediate 221Fr. The 213Bi accumulation was realized in circulation mode which allowed a compact generator design. It was demonstrated that 213Bi could be quickly and effectively extracted from AG MP-50 in form of complexes with various chelating agents including DTPA and DOTA. The performance of the generator presented and a conventional single-column generator on the base of AG MP-50 was tested and both generators were loaded with 225Ac containing 227Ac impurity. The 213Bi generation efficiencies were comparable and greater than 70%, whereas the developed generator provided a deeper degree of purification of 213Bi from Ac isotopes and decay products of 227Ac.